Mini Wind Turbine as An Alternative of Electrical Energy Resources for Navigation Lamps on Fishing Vessel - Dudi Firmansyah; Fis Purwangka; Budhi Hascaryo Iskandar (Fakultas Pertanian Universitas Samudra, 2022)
This study aimed to determine the effect of time (day and night) on the amount of wind speed (km / h) in the study area, to know the type of wind based on average wind speed (km / h) in the study area according to Beaufort scale table, 3 blades and 6 blades on the wind turbine to rotation speed per minute (rpm) of the alternator, knowing the ratio of the battery charging time by wind turbines with 3 blades and 6 blades, knowing the time required to turn on the LED light circuit. This research was conducted by experimental method, which is conducting trials of wind turbine with 3 blades and 6 blades. Data analysis used was univariate, bivariate and advanced analysis. Time (day and night) gives influence to the amount of wind speed. Wind turbine with 6 blades produces a higher alternator (rpm) speed compared to 3 blades. The length of time required to charge the battery ampere to full with 3 blades is 1 hour 45 minutes, while with 6 blades it takes only 1 hour 30 minutes. The energy produced by a mini wind turbine with 6 blades is able to turn on three LED lights (white, red, and green) for 125.6 hours or equal to ± 5 days. Keyword: mini wind turbine